Oriented enstatite inclusions in natural diamond. - Leite, C. R. (1984)
Six crystal inclusions in a twinned diamond from the Tibagi River deposits near Telemaco Borba, Parana State, Brazil, were identified as forsterite (prismatic crystals) and enstatite (tabular crystals, with a 18.17, b 8.81, c 5.17 A). The prismatic forsterite inclusions are oriented along the <110> directions of the host diamond; the main direction of the tabular enstatite crystals is in the same orientation. The identity and orientation of the inclusions were obtained by X-ray precession camera. Enstatite (210) is nearly parallel with the (111) octahedral layer of diamond; a possible epitaxial relationship is discussed.-R.A.H.